PERSEPSI KONSUMEN TERHADAP SEPEDA MOTOR MEREK HONDA BEAT DI KABUPATEN KUTAI KARTANEGARA - Mardiana Mardiana (Prodi Ilmu Administrasi Negara, 2015)
The aim of this research is to know the perception of the consumer of the motorcycle of Honda Trade Mark in Kutai Kartanegara.This research is held in 3 months in . Kutai Kartanegara.The data collection by : Field Work Research by observing and giving questioners., Library Research).The analisis of the data is by Arithmatic Mean; and Chi Square Test.The results of the research are :The average rate of the consumers is that they like the ones which thin body, easily to ride, good striping, effiient and the high sale value.The Honda Beat is good enough. The value of the consumer perception is < than Chi value degrees table (10,597There is no difference betweeen man and womn towards Honda Beat.